2015
DOI: 10.1080/19336934.2015.1126011
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-induced signaling pathways for DUOX-dependent gut immunity

Abstract: Intestinal dual oxidase (DUOX) activation is the first line of host defense against enteric infection in Drosophila. DUOX enzymatic activity is mainly controlled by phospholipase C-β (PLCβ)-dependent calcium mobilization, whereas DUOX gene expression is mainly controlled by the MEKK1-p38 mitogen-activated protein kinase pathway. Furthermore, bacterial-derived uracil molecules act as ligands for DUOX activation. However, our current understanding of uracil-induced signal transduction pathways remain incomplete.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, phospholipase C β (PLCβ) and protein kinase Cα (PKCα), two factors inducing Ca 2+ -mediated activation of DUOXes, are enriched in lipid rafts [ 142 , 143 ], a fact that would predict DUOXes localization to the same site. In support of this hypothesis, a recent publication has linked LR-dependent Ca 2+ signaling to DUOX-mediated ROS generation in Drosophila during pathogenic infection [ 144 ].…”
Section: The Plasma Membrane As a Platform For Redox Signal Transmmentioning
confidence: 99%
“…However, phospholipase C β (PLCβ) and protein kinase Cα (PKCα), two factors inducing Ca 2+ -mediated activation of DUOXes, are enriched in lipid rafts [ 142 , 143 ], a fact that would predict DUOXes localization to the same site. In support of this hypothesis, a recent publication has linked LR-dependent Ca 2+ signaling to DUOX-mediated ROS generation in Drosophila during pathogenic infection [ 144 ].…”
Section: The Plasma Membrane As a Platform For Redox Signal Transmmentioning
confidence: 99%
“…In this pathway, a kind of calcium-dependent cell adhesion molecule, Cadherin 99C, expression levels increase can induce Ca 2+ mobilization together with phospholipase Cβ and protein kinase C. The high Ca 2+ concentration in the cytoplasm initiates DUOX enzymatic activity (Lee et al, 2015a). Additionally, the induction of lipid raft formation, lipolysis, and CaMKII can promote DUOX enzymatic activity (Lee et al, 2018(Lee et al, , 2015b. DUOX-mediated ROS production requires the formation of a DUOX complex rather than an individual DUOX molecule.…”
Section: Duox's Characterizationmentioning
confidence: 99%
“…The Hh pathway also has postnatal roles in defining the immune response which is conserved from flies to humans, although the relevant signaling output and how it is applied as a defense mechanism differs between vertebrates and invertebrates. In a study conducted in Drosophila by Lee et al, Hedgehog signaling was found to be required as a first line of defense against harmful uracil-secreting pathogens in the gut by triggering the production of microbicidal reactive oxygen species (ROS) [ 60 , 95 , 96 ]. Flies expressing RNAis directed to several canonical Hh pathway components showed reduced ROS production upon bacterial infection and a consequent higher mortality rate.…”
Section: Why Might Hh Signaling Be a Frequent Target For Pathogensmentioning
confidence: 99%